GESTION SOCIO-ECONOMIQUE DES MUTUELLES FINANCIERES INFORMELLES DE LA VILLE D’ISIRO - NDENDELE, Chico BOLO; KAYA , Damas ESOLE KESOLE; MUDADRA , Esperance MOGWAMA (IJRDO - Journal of Social Science and Humanities Research, 2021)
The present survey focuses on the socio-economic management of the Mutuelles Financières Informelles (MFIs) in the town of Isiro. The results show that these organisations face enormous constraints in their daily management. These include, among others: insufficient capital, insolvency and embezzlement of funds by members, lack of investment, absence of qualified managers, ignorance of legal texts relating to institutional savings, lack of management control, illegality of MFIs, non-compliance with their statutes and internal regulations, poor performance as well as poor maintenance and/or conservation of administrative and financial documents. By way of therapy, this study proposes the restructuring and efficient management of these mutuals in order to guarantee not only their own development, but also to positively influence the socio-economic development of their social environment.